Inputs, dynamics and potential impacts of silver (Ag) from urban wastewater to a highly turbid estuary (SW France). (January 2017) - Deycard, Victoria N.; Schäfer, Jörg; Petit, Jérôme C.J.; Coynel, Alexandra; Lanceleur, Laurent; Dutruch, Lionel; Bossy, Cécile; Ventura, Alexandre; Blanc, Gérard
Abstract: Although silver (Ag) has been listed as a priority pollutant for the aquatic environment by the European Union (Directive 2006/11/EC), the use of Ag-based products with antimicrobial effects is increasing in Europe, as well as North America and Asia. This study investigates personal care products (PCP) as a potential source of Ag in wastewater, as well as the dynamics and fate of Ag in the influent and effluent of a major urban wastewater treatment plant (WWTP) located on the fluvial part of the Gironde Estuary. Typical household PCPs marked as using Ag contained concentrations of up to 0.4 mg kg −1 making them likely contributors to urban Ag released into the aquatic environment. Silver concentrations in influent wastewater generally occurred during mid-week working hours and decreased during the night and on weekends clearly indicating the dominance of urban sources. Up to 90% of the total Ag in wastewater was bound to particles and efficiently (>80%) removed by the treatment process, whereas 20% of Ag was released into the fluvial estuary. Silver concentrations in wastewater effluents clearly exceeded estuarine concentrations and may strongly amplify the local Ag concentrations and fluxes, especially during summer rainstorms in low river discharge conditions. Further work should focus on environmental effects and fate of urban Ag release due to immediate localized outfall and/or the adsorption on estuarine particles and subsequent release as dissolved Ag chloro-complexes within the estuarine salinity gradient. Highlights: Analysis of Ag along the different steps of the water treatment process at hourly, daily and weekly timescales. Quantification of potential NPAg inputs from personal care products (PCP). Evaluation of the potential fate and impacts of Ag and NPAg concentrations and fluxes on a highly turbid fluvial estuary. Comparison of Ag inputs from urban wastewater with non-urban sources.